Perbedaan Tingkat Defisit Neurologis Pada Stroke Iskemik Lesi Hemisfer Kiri Dan Kanan Di RSUD Dr. MOEWARDI - Prayoga, Muhamad (2016)
Background : Stroke is the second largest cause of death in developed countries and the third largest in the developing world. Stroke will cause neurological deficit that variance depending on damage area of the brain. There is different of anatomy and physiology from left and right hemisphere so if there was damaged, outcome in each hemisphere will be different. Objective: The research was purposed to know the difference of neurological deficit levels in the ischemic stroke left and right hemisphere lesions. Methods: This research is an observational analytic by cross sectional approach. It is carried out in Medical Record Unit of Dr. Moewardi Hospital in November to December of 2015. The Sampling is conducted by purposive sampling technique which uses 58 samples of ischemic stroke patients, It consist of 29 samples left hemisphere lesion and 29 samples right hemisphere lesions.The instrumentation of the research is use data of age, gender, levels of blood glucose, blood pressure, lesions, and NIHSS (National Institutes of Health Stroke Scale) value of the ischemic stroke patients in Dr. Moewardi Hospital. The data is obtained processed using SPSS for Windows 22.0 and analyzed by Mann-Whitney statistically test. Results: The result of this study shows that mean NIHSS left hemisphere lesions are 11.9655 with standard deviation (± 3.417) and left hemisphere lesions was 7,9655 with standard deviation (± 2,211).The result of Mann Whitney test significant value p = 0,001 (p<0,05). Conclusion: Based on this study, can be concluded that there is difference of neurological deficit level's in the ischemic stroke lesions left and right hemisphere.